Respuestas

2012-06-09T18:40:42+02:00

 (-4)         2x-y+7z=8         -8x+4y-28z=-32               

              9x-4y-2z=0          9x-4y-2z=0

                                        x-30z=-32

 

(-5)         2x-y+7z=8           -10x+5-35z=-40

             -3x-5y-10z=21       -3x-5y-10z=21

                                        -13x-45z=-19

 

 (13)       x-30z=-32            13x-390z=-416

             -13x-45z=-19        -13x-45z=-19

                                               -435z=-435

                                              z=-435/-435

                                              Z=1

 

x-30z=-32             9x-4y-2z=0                     verifcaciones:             

x-30*1=-32           9*(-2)-4y-2*1=0             1)  2x-y+7z=8   

x-30=-32              -18-4y-2=0                        2*(-2)-(-5)+7*1=8

x=-32+30              -4y=18+2                         -4+5+7=8

x=-2                     -4y=20                              8=8

                             -y=20/4                     2)9x-4y-2z=0

                              -y=5                            9*(-2)-4*(-5)-2*1=0

                              y=-5                            -18+20-2=0

                                                                     0=0

                                                             3)-3x-5y-10z=21

                                                               -3*(-2)-5*(-5)-10*1=21

                                                              6+25-10=21

                                                                   21=21